Pengaruh Pengalaman Auditor, FEE Audit dan Independensi Terhadap Kualitas Audit: Studi Empiris pada Kantor Akuntan Publik di Wilayah Bekasi - Aureta Zhabila Eka Putri; Amor Marundha; Maidani Maidani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research aims to measure the influence of Auditor Experience, Audit Fees and Independence on Audit Quality at Public Accounting Firms (KAP) in the Bekasi Region. This research was conducted using a non-probability sampling approach with a purposive sampling method. The number of samples used in this research was 62 respondents. The design used in this research is hypothesis testing using the Structural Equitation Model (SEM) - SmartPLS 4.0. The results of this research indicate that (1) Auditor experience has a positive effect on audit quality; (2) Audit Fees have no effect on audit quality; (3) Independence has a positive influence on audit quality.